Running away - Fremon, David K. (New York : Benchmark Books, 1996)
Examines the problems that drive teenagers to run away from home, discusses the hazards of life on the streets, and presents solutions to the problem
Includes glossary
ncludes bibliographical references and index
Primary
Keywords: Runaway teenagers -- United States -- Juvenile literature